Modelling Inflation using Generalized Additive Mixed Models (GAMM) - Zahro, Jamilatuz; Caraka, Rezzy Eko (International Journal Of Chemistry, Mathematics And Physics(IJCMP), 2017)
Inflation becomes an important thing to become a benchmark for economic growth, investor considerations factor in choosing the type of investment, as well as determining factors for the government in formulating fiscal policy, monetary or non-monetary to be run. Inflation calculations carried out using the Consumer Price Index, known as CPI as an indicator to measure the cost of consumption of goods and services markets. Based on an analysis using GAMM was concluded R2 value of 0.996 or can be interpreted that the inflation amounted to 99.6 % can be explained by the variables used in this study and 0.4 % is explained by other factors